First Case in Kazakhstan of Successful Therapy With 2 Consecutive Direct-Acting Antiviral Regimens in a Patient with Hepatitis C Virus-Induced Decompensated Liver Cirrhosis on a Liver Transplant Wait List - Yesmembetov, Kakharman; Ashimkhanova, Aiymkul; Kaliaskarova, Kulpash (Experimental and Clinical Transplantation, 2016)
A 40-year-old man, diagnosed with decompensated liver cirrhosis because of hepatitis C virus, was on the wait list for a liver transplant when he began treatment with the direct-acting antivirals simeprevir 150 mg and sofosbuvir 400 mg. The patient demonstrated end of treatment virologic response at week 12, normal bilirubin, and alanine aminotransferase levels, resolution of ascites, with downgrading to subcompensated liver cirrhosis, and was removed from the liver transplant wait list. However, the patient did not comply with the recommended duration of the antiviral treatment of at least 16 weeks, which resulted in hepatitis C virus relapse at posttreatment week 12. Later, the patient started an alternative regimen that included a combination of ombitasvir 12.5 mg, paritaprevir 75 mg, ritonavir 50 mg, and dasabuvir 250 mg for 24 weeks and achieved a sustained virologic response. However, despite undetectable hepatitis C virus, the patient began to deteriorate again and was again put on the liver transplant wait list. This first described clinical case in Kazakhstan of successful antiviral therapy with 2 consecutive directacting agents demonstrates the importance of virus eradication of pretransplant survival extension and delaying the need for liver transplant.
Keywords: Kazakhstan; hepacivirus; liver cirrhosis